How do families of adolescents with suicidal ideation behave? - Pereira, Maria Gouveia (2014)
The purpose of this study is to analyze how family systems infl uence adolescents’ suicidal ideation. The participants were 534 adolescents (51.1% female and 48.9% male), with ages ranging from 14 to 18 years (M=16.18; SD=1.14). The instruments used were the following: Family Adaptability and Cohesion Evaluation Scale, Psychological Separation Inventory and Questionnaire of Suicidal Ideation. Results have shown that adolescents with higher suicidal ideation belong to the so-called unbalanced families (with low cohesion and fl exibility) and have a confl ictual dependence to their parents. On the other hand, adolescents that belong to balanced families revealed lower suicidal ideation. In conclusion, the family’s cohesion and fl exibility are protective factors against adolescents’ suicidal ideation.